Adverse Effects of Covid-19 Vaccine; an Observational Studymainly Focusing on the Cutaneous Reactions in Both Genders - Syeda Shahmoona Tirmizi, Adnan Anwar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: COVID-19 caused a deleterious impact on the health care system globally.The roll out of vaccines seems to be the only effective way to curtail the spread of disease.The purpose of this study is to assess the dermatological adverse effect of post COVID-19vaccination on a gender basis. Methodology: This was an observational,cross-sectional,questionnaire-based survey conducted in Pakistan.The sample comprises 518 participants. The questionnaire was self-designed. The trial lasted six months, from August 1, 2022, until January 31, 2023. We used a non-probability sampling technique.Dermatological adverse effects like burning pain, redness, rashes, and lymphadenopathy at the injection site were recorded.Fever was also noted. All the participants have received booster shots or double doses of any one of CCOVID-19 vaccines, such as AstraZeneca, Pfizer, Sinovac, Sinopharm,Pakvac, etc. A p-value of less than 0.05 was considered statistically significant.Qualitative data was reported as frequency and percentage, and quantitativedata was reported as standard deviation and mean. Results: The study included 518 subjects, of whom 262 were males and 256 were females. The mean age of male is 42.70±14.05 years and female is 39.04±14.6years with a significant difference observed between them (p=0.004). The most common complaint among dermatological adverse effects after first was pain. 106(40.5%) male and 132(51.6%) female reported painwith a significant difference observed between them (p=0.011) followed by swelling which was reported by 92(35.1%) males and 120(46.9%) females with a significant difference observed between them (p=0.006).Burning was reported in 92(35.1%) male and 148(57.8%) female with a significant difference observed between them(p<0.001). Fever was also quite commonly reported in both male 116(44.3%) and female 178(69.5%) with significantdifference observed between them (p<0.001),Likewise post 2nd dose of vaccination, pain was most commonly noted in 90(34.4%) male and female 124(48.4%) female with significant difference observed between them (p=0.001). Moreover, burning was reported by 80(30.5%) malesand 132(51.6%) females with a significant difference observed between them (p<0.001). rashes were reported by76(29.0%) males and 100(39.1%) females with a significant difference observed between them (p=0.016), lymphadenopathy was also significantly associated with genders, (p<0.001). Conclusion: This study concluded that the burning pain,redness,rashes,and lymphadenopathywere the most prevalent side effects in male and female post 1st and 2ndCOVID-19 vaccination.Furthermore fever was also reported in majority of subjects.In addition to this higher percentage of side effects were recorded in females as comparedto males. Keywords: COVID-19 vaccination, vaccine adverse effects, pain, fever.